Tax System Evaluation Model in the Context of Entrepreneurship Promotion: Theoretical Aspect - Giriuniene, Gintare; Giriunas, Lukas; Cernius, Gintaras (International Journal of Economics and Financial Issues, 2016)
A model for evaluation of the tax system in the context of entrepreneurship promotion consisting of four stages was formed upon analysis of scientific readings. Analysis of the quantitative variables in evaluation of the tax system in the context of entrepreneurship promotion is made and the dimensions of self-employed persons and companies are evaluated in terms of quantity in the first stage. A matrix for identification of the type of the tax system is formed in the second stage of the model. The third stage of the formed model serves for establishment of the frequency of occurrence of the variables typical to one or another type of countries in the qualitative evaluation of the tax system in the context of entrepreneurship promotion. Based on the results of the second and the third stages of the model, a list of quantitative and qualitative of variables of the tax system typical to one or another type of counties in the context of entrepreneurship promotion is made during the fourth stage. Based on this, a country can anticipate respective priorities for formation of the tax system in order to promote or limit entrepreneurship of certain dimensions in the country. Keywords: tax system, entrepreneurship, evaluation model. JEL Classifications: E60, L26.